Efforts to Improve Mathematics Learning Outcomes Using Napier Bone Teaching Aids for Elementary School Students - Fakhroni, Ahmad Alfiyan; Puotier, Zutaah (Interval: Indonesian Journal of Mathematical Education, 2023)
Purpose of the study: This research aims to improve mathematics learning outcomes in multiplication calculation operations using Napier bone teaching aids so that an active, creative, enjoyable learning process can be produced and ultimately complete learning outcomes can be achieved. Methodology:This research was conducted using mixed methods, namely quantitative methods and qualitative methods. The qualitative method was carried out using a type of classroom action research. Meanwhile, quantitative methods use observation techniques, and formative tests are analyzed using descriptive techniques. The sample for this research was 33 fourth grade elementary school students, consisting of 16 boys and 17 girls. The sampling technique uses simple random sampling. Data analysis techniques use percentage statistics and qualitative using miles and huberman. Main Findings: The results of observations carried out in cycle I followed by a formal test showed data in the form of a class average result of 45.75. In cycle II the average student formal test result was 61.21 and the difference between cycles I and II proved that there was an increase in student learning outcomes. In cycle III the average formal test result was 72.12. Meanwhile, the students' achievement of the Minimum Completeness Criteria ) has been achieved in accordance with the class KKM achievement standard, namely 87.9%. Novelty/Originality of this study: The novelty of this research is that it is a means of creating interesting activities and games that encourage direct learning and foster a deeper understanding of multiplication.